Hepatic arterial infusion chemotherapy with cisplatin and sorafenib in hepatocellular carcinoma patients unresponsive to transarterial chemoembolization: A propensity score‐based weighting. Issue 3 (March 2015) - Kondo, Masaaki; Morimoto, Manabu; Ishii, Tomohiro; Nozaki, Akito; Fukuda, Hiroyuki; Numata, Kazushi; Kobayashi, Satoshi; Ohkawa, Shinichi; Hidaka, Hisashi; Nakazawa, Takahide; Shibuya, Akitaka; Okuse, Chiaki; et al.
Abstract : Objective: We aimed to evaluate the efficacy and tolerability of hepatic arterial infusion chemotherapy (HAIC) using cisplatin as an alternative to sorafenib for the treatment of hepatocellular carcinoma (HCC) patients who had not responded to transarterial chemoembolization (TACE). Methods: Medical records of 127 consecutive HCC patients without extrahepatic metastasis (cisplatin, n  = 44; sorafenib, n  = 83) who had not responded to prior TACE at four institutions were retrospectively reviewed. An inverse probability of treatment weighting using propensity scoring was used to adjust for the selection bias. Results: Severe adverse events accounting for treatment discontinuation occurred in 2.3% of the patients in the cisplatin group and 32.5% of those in the sorafenib group. The median overall survival (OS) period was 11.2 months (95% CI 4.8–17.7) in the cisplatin group and 10.2 months (95% CI 8.8–11.5) in the sorafenib group, respectively. After an inverse probability of treatment weighting adjustment, the survival outcome of the HAIC treatment group was not inferior to that of the sorafenib treatment group (hazard ratio 0.758; 95% CI 0.471–1.219, P  = 0.253). Conclusion: HAIC with cisplatin can be an alternative treatment for the selection of HCC patients who have not responded to prior TACE and cannot tolerate sorafenib.